Jidišismy, bohemismy a prvky středoevropského jazykového svazu v paměti českých Němců: Slovník české němčiny jako příklad strážce jazykové a kulturní paměti - Balík, Štěpán (Poznańskie Studia Slawistyczne, 2019)
In the collective memory of Czech Germans as it is saved and presented in published volumes of Sudetendeutsches Wörterbuch and its Catalogue in Gießen (Collegium Carolinum), there are not only many cases of Bohemisms, but also Yiddishisms. Some of them are part of the Central European League vocabulary. In my survey, I analysed and classified several dozen Czech German Yiddishisms, showing that their semantics correspond with the heterostereotypical picture of a Jew itself. Designation of a Jew in Czech German are mostly negative or they indicate a depreciative meaning. On the other hand, a few of them are of a very positive sense. Consequently, so called core and cultural borrowings (Myers-Scotton, 2008) from Yiddish represent specific predominantly negative semantic categories. In addition, in most of the cases, the Yiddish cultural borrowings shift in semantics from simple cultural references to core borrowings through their connection to metaphoric meaning.